Delito de colusión como práctica de funcionarios en la administración de recurso del Estado, en el gobierno regional de Huancavelica, durante el año 2020 - Ventura Riveros, Fredy Willy (2021)
The purpose of this research was to demonstrate that collusion acts carried out in the administration of the regional government of Huancavelica were an administrative reality affecting the entire public sector, especially regarding the inadequate management of the economic resources of each regional government and the criminal behaviors of officials responsible for leading the country, region, province, or district of our nation. To this is added the formulation of the hypothesis: Why do public officials have the practice of corruption in managing state resources? This question demanded a detailed investigation of the causes, consequences, and alternatives to mitigate these malpractices that have repercussions on the development of communities and the mismanagement of state resources. The entire problem statement, hypothesis, and research work required the systematic application of a method. In this case, the descriptive method was chosen, as the research was carried out directly in the Regional Government of Huancavelica, analyzing public tender files conducted during the year 2020. It is worth mentioning that the problem statement arises from reality, context, a situation in all its dimensions; in this case, from the administration of state resources and the negative behavior exhibited by those in positions of authority concerning the resources entrusted to them for the benefit of an entire society that has multiple needs and demands to meet to achieve the status of a human being, which the law and the state strive to address. In support of this work, charts and tables were employed, providing a detailed insight into certain aspects related to the research topic. Additionally, on-site or referential sources of information, such as bibliographies containing valuable data on the subject matter, were consulted.